EFFECT OF VARIOUS FERTIGATION SCHEDULES AND ORGANIC MANURES ON TOMATO (LYCOPERSICON ESCULENTUM MILL.) YIELD UNDER ARID CONDITION - SINGH, AJEET; I. J. GULATI,; CHOPRA, RAHUL (The Bioscan, 2013)
Effect of various fertigation schedules and organic manures on tomato (Lycopersicon esculentum Mill.) was evaluate yield and fertilizer use efficiency under arid condition. The results showed that application of compost 5 t ha-1 + 2 t ha-1 lignite significantly increased the average fruit weight, fruit yield per plant, fruit yield and fertilizer use efficiency. Daily method of fertigation maximum increased average fruit weight, fruit yield per plant, fruit yield and fertilizer use efficiency over conventional method of fertilizer application. Highest average fruit weight, fruit yield per plant and fruit yield were registered with 100% recommended dose of NPK as compared to 2/3rd recommended dose of NPK fertilizer. It can be concluded that application of compost 5 t ha-1 + 2 t ha1 lignite, daily method of fertigation and 100% recommended dose of NPK fertilizer resulted better as compare to other treatments. These results are only indicated and based on one-year experimentation and required to arrive at more consistent and definite conclusion for recommendation to the farmers.